Effects of low molecular weight soybean peptide on mRNA and protein expression levels of differentiation markers in normal human epidermal keratinocytes. Issue 6 (3rd June 2014) - Tokudome, Yoshihiro; Nakamura, Kyosuke; Hashimoto, Fumie
Abstract: Low molecular weight soybean peptide (LSP) was applied to normal human epidermal keratinocytes, and the results showed a significant increase in the gene expression levels of involucrin, transglutaminase, and profilaggrin. Filaggrin protein levels were also significantly higher. It is possible that LSP has an epidermal cell differentiation-promoting effect and may be able to regulate metabolism of the epidermis.